2018
DOI: 10.1007/s13300-018-0482-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral Antidiabetic Drugs as Add-On Treatments in Patients with Type 2 Diabetes Uncontrolled on Metformin: A Network Meta-Analysis

Abstract: We assessed the efficacy and safety of oral antidiabetic drugs (OADs) as an add-on treatment in patients with type 2 diabetes uncontrolled on metformin. PubMed, the Cochrane Library, and Embase were searched from inception to October 20, 2017. Pairwise and network meta-analyses were conducted using Stata 14.1 software. Odds ratios (ORs) and weighted mean differences (WMDs) were used to evaluate outcomes. Sixty-eight trials including 36,746 patients were analyzed. No significant differences in the risk of major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Concerns regarding sulfonylureas and cardiovascular complications have been addressed by a number of studies showing no difference in the risk of major adverse cardiovascular events or all-cause mortality between second-generation sulfonylureas and other classes of oral glucose-lowering agents [14,38,48,49]. The ADVANCE trial found that, compared to standard control, intensification of gliclazide modified release (MR) treatment was associated with long-term benefits on microvascular end points (new or worsening nephropathy and new or worsening retinopathy) in addition to effective glycaemic control [25].…”
Section: Macrovascular Complicationsmentioning
confidence: 99%
“…Concerns regarding sulfonylureas and cardiovascular complications have been addressed by a number of studies showing no difference in the risk of major adverse cardiovascular events or all-cause mortality between second-generation sulfonylureas and other classes of oral glucose-lowering agents [14,38,48,49]. The ADVANCE trial found that, compared to standard control, intensification of gliclazide modified release (MR) treatment was associated with long-term benefits on microvascular end points (new or worsening nephropathy and new or worsening retinopathy) in addition to effective glycaemic control [25].…”
Section: Macrovascular Complicationsmentioning
confidence: 99%
“… Metformin is associated with low rates of hypoglycaemia when compared with other oral therapies and is thus preferred during Hajj as long as it is well tolerated by the patient and the glomerular filtration rate is > 30 mL/min/1.73 m 2 [ 47 ]. In the absence of contraindications, sodium-glucose co-transporter-2 SGLT2 inhibitors can be used in combination with metformin to further reduce the risk of hypoglycaemia [ 44 ].…”
Section: Management During Hajjmentioning
confidence: 99%
“…Metformin is associated with low rates of hypoglycaemia when compared with other oral therapies and is thus preferred during Hajj as long as it is well tolerated by the patient and the glomerular filtration rate is > 30 mL/min/1.73 m 2 [ 47 ].…”
Section: Management During Hajjmentioning
confidence: 99%
“…Since monotherapy may fail to achieve its goal in reaching glycemic control in individuals with T2DM [ 5 ], combination therapy is usually required and should involve agents with different and complementary mechanisms of action [ 6 ]. Recent studies show that early combination therapies were associated with better glycemic control [ 7 ].…”
Section: Introductionmentioning
confidence: 99%